Left Functional Pneumonectomy Caused by a Very Rare Giant Intrathoracic Cystic Lesion in a Patient with Gorham–Stout Syndrome: Case Report and Review of the Literature - Nikolaos Tasis; Ioannis Tsouknidas; Argyrios Ioannidis; Konstantinos Nassiopoulos; Dimitrios Filippou (Case Reports in Pulmonology)
Gorham–Stout syndrome is an uncommon entity, with few cases reported in bibliography. It consists of osteolytic manifestations affecting various bones and replacing them with lymphangiomatous tissue. With pathophysiology unknown, Gorham–Stout disease affects also cardiorespiratory system usually causing lytic lesions to the bones of the thoracic cage or directly invading the thoracic duct. This is a case report of a unique respiratory manifestation of the disease and a review of its cardiorespiratory complications.